A Universal Ultracentrifuge Spectrometer Visualizes CNT-Intercalant-Surfactant Complexes - Karabudak, Engin; Backes, Claudia; Hauke, Frank; Schmidt, Cordula; Cölfen, Helmut; Hirsch, Andreas; Wohlleben, Wendel (ChemPhysChem, 2010)
Reel them in: Wavelength-resolved movies of the centrifugal fractionation of a single-walled carbon nanotube dispersion (see picture) are used to obtain the composition and absorption profiles of all fractions even in a complex dispersion, where nanotubes have been efficiently solubilized by an intercalant-surfactant mixture. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.